Speculation In Islamic Finance Market - Kettab, Hayet (Université de M'sila, 2018)
Abstract This study aims to clarifies the meaning of speculation in islamic jurisprudence and economy ,also its Types and conditions , We find that there is a difference between legitimate speculation in shares known in Islamic jurisprudence , and speculation in financial market ,the first is one of the main means of investing in Islamic economy, and it is one of the most important formulas that Presented by scholars as essential method than usury, the second is investing money in buying and selling shares to take advantage of the company returns. In Islamic jurisprudence some of the scholars permit the selling and buying of shares in financial market with conditions, they see that the work in financial market take different forms permissible and forbidden, so they require legitimate conditions to deal in the financial market in order to bargains for avoid financial difficulties. Key words: Speculation , Financial market , Economy, Islamic Jurisprudence ملخص تهدف هذه الدراسة إلى بيان مفهوم المضاربة في الفقه الإسلامي والاقتصاد الوضعي، وكذا أنواعها وشروطها، حيث نجد أن هناك فرقا بين المضاربة المشروعة في الأسهم المعروفة في الفقه الإسلامي، والمضاربة في الأسواق المالية ، فالأولى هي أحدى الوسائل الرئيسية للاستثمار في الاقتصاد الإسلامي، كما تعتبر من أهم الصيغ التي قدمها العلماء كبديل أساسي للربا، والثاني هي استثمار الأموال في شراء وبيع الأسهم للاستفادة من أرباح الشركة. في الفقه الإسلامي بعض العلماء يجيزون بيع وشراء الأسهم في سوق المال بشروط ، ويرون أن العمل فيه يتخذ أشكالا مختلفة جائزة وممنوعة، حيث يتطلب الأمر شروط شرعية للتعامل في سوق المال من أجل تجنب الصعوبات المالية.
Keywords: المضاربة ; سوق المال ; اقتصاد ; الفقه الإسلامي .